2022
DOI: 10.1155/2022/1817721
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Sequencing Analyses Revealed Heterogeneity and Dynamic Changes of Metabolic Pathways in Astrocytes at the Acute Phase of Ischemic Stroke

Abstract: Astrocyte plays important roles in the pathogenesis of ischemic stroke and reperfusion injury. They intensively participate in the energy metabolism of the brain, while their heterogeneity and function after ischemic stroke remain controversial. By employing single-cell sequencing of mice cortex at 12 h after transient middle cerebral artery occlusion (tMCAO) and comparing with the similar published datasets of 24h after tMCAO, we uncover the cellular phenotypes and dynamic change of astrocytes at the acute ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…Our results and other studies ( Li et al, 2016 ; Hockley et al, 2019 ; Renthal et al, 2020 ; Parpaite et al, 2021 ; Wang et al, 2021 ) have shown that neurons in the peripheral ganglion have distinct subpopulations that are consistent with neurons of different functions, but there are fewer relevant studies on SGCs subtypes in the peripheral ganglion. Astrocytes, as glial cells similar to SGCs in the CNS, a series of correlative studies based on scRNA-seq have demonstrated the diversity of astrocytes in different regions of the brain and the variation of astrocyte subtypes in different disease ( Batiuk et al, 2020 ; Hasel et al, 2021 ; Hou et al, 2022 ; Ma et al, 2022 ; Sadick et al, 2022 ). Compared to astrocytes, there are currently fewer studies on single-cell transcription of SGCs subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results and other studies ( Li et al, 2016 ; Hockley et al, 2019 ; Renthal et al, 2020 ; Parpaite et al, 2021 ; Wang et al, 2021 ) have shown that neurons in the peripheral ganglion have distinct subpopulations that are consistent with neurons of different functions, but there are fewer relevant studies on SGCs subtypes in the peripheral ganglion. Astrocytes, as glial cells similar to SGCs in the CNS, a series of correlative studies based on scRNA-seq have demonstrated the diversity of astrocytes in different regions of the brain and the variation of astrocyte subtypes in different disease ( Batiuk et al, 2020 ; Hasel et al, 2021 ; Hou et al, 2022 ; Ma et al, 2022 ; Sadick et al, 2022 ). Compared to astrocytes, there are currently fewer studies on single-cell transcription of SGCs subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 hour acute time point is critical because it is a clinically accessible time point for delivery of future therapies, and our data provides the first published resource describing it. The next earliest astrocyte and microglial transcriptomes after stroke were 12 hours after stroke (Ma et al, 2022; Zheng et al, 2022). Other advantages of our study are the high number of biological replicates, use of both sexes, and high sequencing depth (>12 million reads per sample).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AIS reduces the correlation between fibroblasts and other cells ( Zheng et al, 2021 ). Similarly, 24 h after ischemia–reperfusion, astrocytes can act as a signal amplifier to release inflammatory signals such as cytokines and attract assistance from distal sites ( Figure 1 ; Ma et al, 2022 ).…”
Section: Participate In Inflammatory Reactionmentioning
confidence: 99%
“…ScRNA-seq provided an essential clue for analyzing the role of the Wnt signaling pathway in patients with ischemic stroke. A recent study found that astrocytes play an independent neuroprotective role 12 h after ischemia–reperfusion, mainly manifested by the activation of oxidative phosphorylation, gap junction and tight junction, ferroptosis, and other pathways ( Ma et al, 2022 ).…”
Section: Promote Nerve Repairmentioning
confidence: 99%